2015
DOI: 10.1108/jabs-03-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transformational leadership on employee creativity: the role of learning orientation

Abstract: Purpose – This research aims to explore the relationship between transformational leadership and employee creativity. In addition, we intend to study the moderating role played by learning orientation in the relationship between transformational leadership and employee creativity. Design/methodology/approach – Data have been collected from employees working at the Airtel and Aircel call centers of J&K (India). A two-step approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(179 citation statements)
references
References 90 publications
14
124
1
14
Order By: Relevance
“…This result is consistent with previous studies (Calantone et al, 2002;Rhee et al, 2010;Sheng & Chien, 2016) in which learning orientation showed to be closely related to innovative activities of the organization. If there is a learning orientation in an organization, a desire to develop learning activities like investment in education and training (Calantone et al, 2002;Jyoti & Dev, 2015), creation and implementation of knowledge (Baba, 2015), collecting knowledge and information from different sources (Abdulai Mahmoud & Yusif, 2012), sharing knowledge across the organization and acceptance of new ideas (Calantone et al, 2002) promote. As a result, new knowledge is acquired from different sources, especially external ones and its combination with existing knowledge of the organization leads to new and innovative ideas and initiatives.…”
Section: -Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous studies (Calantone et al, 2002;Rhee et al, 2010;Sheng & Chien, 2016) in which learning orientation showed to be closely related to innovative activities of the organization. If there is a learning orientation in an organization, a desire to develop learning activities like investment in education and training (Calantone et al, 2002;Jyoti & Dev, 2015), creation and implementation of knowledge (Baba, 2015), collecting knowledge and information from different sources (Abdulai Mahmoud & Yusif, 2012), sharing knowledge across the organization and acceptance of new ideas (Calantone et al, 2002) promote. As a result, new knowledge is acquired from different sources, especially external ones and its combination with existing knowledge of the organization leads to new and innovative ideas and initiatives.…”
Section: -Discussion Of the Resultsmentioning
confidence: 99%
“…Organizational learning orientation as a derivation from the organizational learning theory is described as a wide range of activities related to the creation and use of knowledge (Calantone, Cavusgil, & Zhao, 2002;Fang et al, 2014) and orients the organization in direction of learning. It consists of four dimensions: commitment to learning, shared vision, open-mindedness and intra-organizational knowledge sharing (Calantone et al, 2002;Jyoti & Dev, 2015). Commitment to learning indicates organization's desire to develop learning activities (Calantone et al, 2002;Sinkula, Baker, & Noordewier, 1997) and it has a significant impact on its investment in education and training.…”
Section: Learning Orientation and Its Relationship With Innovation Pementioning
confidence: 99%
“…The Cronbach’s alphas from the present study indicated excellent reliability for transformational leadership (α=0.96) and passive-avoidant leadership (α=0.86), and good reliability for transactional leadership (α=0.76). The validity of the MLQ is supported by studies demonstrating its associations and prediction of important organizational outcomes including change in practice (Leithwood & Jantzi, 2006), attitudes toward EBIs and capacity to train providers and implement EBIs (Aarons, 2006; Bonham, Sommerfeld, Willging, & Aarons, 2014), organizational culture (Aarons, Ehrhart, Farahnak, Sklar, & Horowitz, In press), knowledge sharing (Chen & Barnes, 2006), employee creativity (Dhar, 2015; Jyoti & Dev, 2015), innovation performance (Saad & Mazzarol, 2014), enhanced EBI receptivity, ongoing use, and ability to implement and sustain EBIs (Stetler, Ritchie, Rycroft-Malone, Schultz, & Charns, 2009), organizational climate expectations (von Thiele Schwarz, Hasson, & Tafvelin, 2016), and patient and consumer outcomes (Corrigan, Lickey, Campion, & Rashid, 2000; Wong & Giallonardo, 2015). Home visitors indicated the extent to which their supervisor exhibited specific behaviors on a 5 point Likert-type scale from “Not at all” to “To a very great extent.” Individual leadership scores were computed as item averages.…”
Section: Methodsmentioning
confidence: 99%
“…The findings gained from individualized consideration are coaching, nurturing, respecting others, and organizational values. The resulting impact is that students who are members of paskibra can teach their skills to new prospective paskibra and strengthen the relationship between senior and junior (Jyoti and Manisha, 2015). Idealized influence is that a leader seeks to influence his followers through direct communication by emphasizing the importance of commitment and belief, and has a determination to achieve the goals (Antonakis, et al, 2003, Rafferty and Griffin, 2004, and Antonakis, 2012.…”
Section: Table 1 Major Propositional Formulations Obtained In the Studymentioning
confidence: 99%
“…According to (Hartog, et al, 1997), (Yammarino and Dubnisky, 1994), (Antonakis, et al, 2003), (Avolio, 2005), and (Dionne, et al, 2004) in Jyoti and Manisha 2015), states that Inspirational motivation defines inspiration as a leader's capacity to act as an example for his followers. Inspirational motivation refers to the way leaders take decisions to inspire their followers to achieve personal and organizational goals.…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%